Therapeutic factors and biomaterial-based delivery tools for degenerative intervertebral disc repair - Song, Haoyang; Guo, Chuan; Wu, Ye; Liu, Yuheng; Kong, Qingquan; Wang, Yu (Frontiers in Cell and Developmental Biology, 2024)
Intervertebral disc degeneration (IDD) is the main cause of low back pain (LBP), which significantly impacts global wellbeing and contributes to global productivity declines. Conventional treatment approaches, encompassing conservative and surgical interventions, merely serve to postpone the advancement of IDD without offering a fundamental reversal. Consequently, there is an urgent demand for an effective approach to prevent the progression of IDD. Recent investigations focusing on the treatment of IDD utilizing diverse bioactive substances integrated within various biomaterials have exhibited promising outcomes. Various bioactive substances, encompassing conventional small molecule drugs, small molecule nucleic acids, and cell therapies, exhibit distinct capacities for repairing IDD. Additionally, various biological material delivery systems, such as nano micelles, microspheres, and hydrogels, possess diverse biological and release characteristics. Consequently, these diverse materials and drugs hold promise for advancing the treatment of IDD. This article aims to provide a concise overview of the IDD process and investigate the research advancements in biomaterials and bioactive substances for IDD treatment, delving into their mechanisms.